Repetitive nanosecond all-solid-state pulsers based on SOS diodes; Proceedings of the 11th IEEE International Pulsed Power Conference, Baltimore, MD, 29 june-2 july, 1997; Vol. 2 - Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Rukin S. N.; Slovikovskii B. G. (1997, 1997)
В фонде НТБ ТПУ отсутствует